Comparative Study of Cat’s Whiskers Leaves (Orthosiphon stamineus) and Mint Leaves (Mentha arvensis) as Repellent For Houseflies - Surahmaida Surahmaida; Cicik Herlina Yulianti (Jurnal Biologi Tropis, 2023)
House flies (Musca domestica) are one of the challenging pests that are difficult to overcome and control. Common control methods usually involve the use of chemical insecticides, but a more environmentally friendly alternative is to use plant-based insecticides with repellent properties. Medicinal plants from the Lamiaceae family are famous for their distinctive aroma and are effective in treating pest problems. This research aims to evaluate the potential of cat's whisker leaves and mint leaves as housefly repellent. The repellency test used cotton impregnated with extract concentrations of 2,000 ppm, 4,000 ppm, 6,000 ppm, 8,000 ppm and 10,000 ppm. Exposure time was 30 minutes and carried out 3 times. The repellency percentage is then calculated. The results of the research showed that at concentrations of 2,000 ppm and 4,000 ppm there were still some flies landing, but at concentrations of 6,000 ppm, 8,000 ppm and 10,000 ppm no flies landed. Strong repulsion was observed at concentrations of 2,000 ppm (86.7% for cat's whisker leaf extract and 82.7% for mint leaf extract) and 4,000 ppm (96% for cat's whisker leaf extract and 88% for mint leaf extract). Both extracts showed very strong repulsion (100%) at concentrations of 6,000, 8,000 and 10,000 ppm. These results show that the higher the concentration, the stronger the repellent effect produced. In conclusion, cat's whiskers and mint leaves have potential as active mosquito repellent ingredients, and this research can be the basis for further development as a pest control method, especially against houseflies.